Potentiality of MWCNT on 3D-printed bio-inspired spherical-roof cubic core under quasi-static loading - Ma, Quanjin; Rejab, M. R. M.; Abu Hassan, Shukur; Hu, Haichao; Kumar, A. Praveen (Elsevier Ltd., 2022)
Sandwich panel is increasingly used as lightweight energy absorbing components, which provides excellent crashworthiness performance with the three-dimensional periodic core. This paper investigates 3D-printed bio-inspired spherical-roof cubic cores with multi-walled carbon nanotubes (MWCNT) and foam-filled cores under quasi-static loading. The proposed bio-inspired spherical-roof cubic cores with 1.5 mm wall thickness were manufactured using the fused filament fabrication process, which used 70% polylactic acid (PLA) and 30% carbon fiber filament. Moreover, four groups of 3D-printed bio-inspired spherical-roof cubic cores were compared and analyzed on compressive properties and failure behavior. Experimental results were shown that foam-filled double bio-inspired spherical-roof cubic core with MWCNT was the maximum Fpeak with 1.92 kN, which provided a much more stable plateau load and better energy-absorbing characteristics. In addition, it is conducted that a double bio-inspired spherical-roof cubic core with four notches core is considered as the potential energy-absorbing core.